Compression after impact of CFRE composites immersed in distilled water. Issue 5 (3rd September 2021) - Othman, Ramzi; Khashaba, U.A.; Almitani, Khalid H.
Abstract: This work is interested in the effect of water immersion on the low-velocity impact behaviour of carbon fiber reinforced epoxy composites. The woven composite laminates are manufactured using the prepreg technique. The specimen preparation and the impact tests are undertaken following the ASTM D 7136 standard. To ensure water saturation, the specimens were immersed in distilled water up to 368 h. The moist specimens were subjected to impact energies ranging between 15 and 85 J. The impact results and the compression-after-impact (CAI) properties are compared with those obtained under dry testing conditions. The moist composites show more significant damage reduction than the dry one. Larger damage area is also expected for wet plates when CAI strength is compared to the strength of notched specimens. Several equations have been proposed namely to model the threshold force, the peak force, the normalised absorbed energy, the normalised CAI strength and the strength of notched plates. All these equations show good agreement with experimental data.